Binge eating disorder and body uneasiness - Cuzzolaro, Massimo (Array, 2008)
Summary: Debate continues regarding the nosological status of binge eating disorder (BED) and the specific diagnostic criteria, including whether, like anorexia nervosa and bulimia nervosa, it should be characterized by body image disturbances in addition to abnormal eating behaviour. The aims of this article are: a) to concisely review the main points of the literature that has developed on diagnosis and treatment (especially pharmacological) of BED and b) to present the results of an original research on body image in obese patients with BED. The study was aimed to verify the following hypothesis: in persons with obesity, BED is associated with greater body uneasiness independently of some possible modulating factors. We studied a clinical sample of 159 (89 females and 70 males) adult obese patients who fulfilled DSM-IV-TR diagnostic criteria for BED matched to 159 non-BED obese patients for gender, ethnicity, BMI class, age, weight, stature, onset age of obesity, education level, and marital status. We used the Body Uneasiness Test (BUT), a valuable multidimensional tool for the clinical assessment of body uneasiness in subjects suffering from eating disorders and/or obesity. Obese patients with BED reported higher scores than non-BED patients in the General Severity Index (BUT-A GSI) and in every BUT-A subscale. All differences were statistically significant in both sexes. As expected women obtained higher scores than men. According to some other studies, our findings suggest that a negative body image should be included among diagnostic criteria for BED. Consequently, treatment should be focused not simply on eating behaviour and outcome studies should evaluate changes of body image as well. Keywords: binge eating disorder, obesity, body image, Body Uneasiness Test, drug treatment